AGRESIVITAS PELAPORAN KEUANGAN DAN PENGHINDARAN PAJAK - Andyan Zakiy Pradhana; Arif Nugrahanto (Politeknik Keuangan Negara STAN, 2021)
Identification of tax avoidance is one of the substantial issues for tax authorities. Success in this stage ensure optimal tax compliance. To do that, financial statements become the object of critical analysis. This study seeks to identify the effect of financial statements (aggressive) on tax avoidance. The mineral and coal mining sector is chosen as the sample because it is one of the business sectors with a fairly high level of tax avoidance. There are 26 companies on the IDX that are the samples of this study. By regressing fixed effect panel data in the form of financial reports for 2012-2018, the results show that aggressive financial reporting has a positive effect on tax avoidance. With a confidence level of 99%, every 1% increase in the level of aggressiveness of financial reporting equivalent to an increase in tax avoidance efforts of 4.6%. For tax authorities, these findings can be used to assess the risk of non-compliance by taxpayers.